Por que você não o surrou em vez de matá-lo? : a organização social da violência no início do século XX - Curitiba, 1900 - 1911 - Hatschbach, Matheus, 1995- (2021)
Orientador: Prof. Dr. Carlos Alberto Medeiros Lima